Analysis of Cyber Criminal Law on The Protection of Electronic Medical Records (Study at Premier Medika Partner Hospital Medan) - Esti Rahayu; M. Sinaga (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
In today's digital era, the development of information technology has revolutionized various aspects of human life, including in the health sector. The use of electronic medical records in hospitals has become a common standard, allowing for more efficient storage of patient data and faster access for medical personnel. However, along with this progress, legal challenges have also emerged, especially related to the protection of patient personal data. The issues discussed are how the implications of cyber criminal law affect the protection of electronic medical records in hospitals, how the obstacles and barriers are in protecting electronic medical records at Mitra Medika Premier Hospital Medan and how cyber crime prevention efforts are in protecting electronic medical records at Mitra Medika Premier Hospital Medan. The research used empirical juridical by using data collection methods through field research and library research. Library studies are obtained by reading, studying and reviewing books, laws and regulations, journals or data in the form of library materials while field studies are conducted using interview methods. Some forms of violations that may occur in the management of electronic medical records at Mitra Medika Premier Hospital Medan are Unauthorized Access: When the login of an absent health worker is entrusted to another health worker to replace data entry and Data Retrieval: Patient data is used by unauthorized parties, for example laboratory result photos. Efforts made by Mitra Medika Premier Hospital Medan in protecting Health data include: Strengthening Technology Infrastructure: Implementation of firewalls, antiviruses, and data encryption, Routine Audits: Ensuring the system runs according to security standards, Increasing Staff Awareness: Regular training related to data protection and Updates/development of information technology systems, especially related to data security.